Trapped in America's safety net one family's struggle - Campbell, Andrea Louise 1966- (Chicago studies in American politics, 2014)
When the author's sister-in-law, Marcella Wagner, was run off the freeway by a hit-and-run driver, she was left paralyzed from the chest down. Like so many Americans, neither Marcella nor her husband, Dave, had health insurance. Using Marcella and Dave's situation as a case in point, the author reveals the system's many shortcomings.